Menelisik Persepsi Dosen PTKIN Tentang Gerakan Islam Radikal Di Indonesia - As’ad, Mahrus; Kurniasih, Siti (Universitas Islam Negeri Raden Intan Lampung, 2023)
There is a crucial issue in several campuses namely the spread of radicalism and terrorism which has begun to target students on campus.The understanding is actually a simplification which results in the difficulty of capturing the substantive meaning of the two terms. The various perceptions of PTKIN lecturers about the meaning of